Cerebrospinal fluid and serum cytokine profiles in severe viral encephalitis with implications for refractory status epilepticus: a retrospective observational study - Huang, Peipei; Yang, Fan; Dong, Ruirui; Wen, Lijun; Zang, Qiuling; Song, Dandan; Guo, Junshuang; Wang, Yating; Zhang, Ruike; Ren, Zhiping; Qin, Jinjin; Teng, Junfang; et al. (Frontiers in Immunology, 2025)
BackgroundTo identify new intervention targets, we explored the correlation between cytokines and the development of refractory status epilepticus (RSE) in patients with severe viral encephalitis (SVE).MethodsWe examined the characteristics of 14 cytokines in the cerebrospinal fluid (CSF) and serum, analyzing their correlation with acute symptomatic seizures and prognosis. Furthermore, we conducted a dynamic analysis of differences and correlations in the expression of cytokines among patients with SVE without seizures, those with controlled seizures, and those with RSE.ResultsWe included 161 patients with SVE; the incidence of seizures was 55.2%, and the mortality rate was 5.5%. Notably, 18.9% of these patients developed RSE, with a mortality rate of 20%. During the early stage of SVE, CSF interleukin (IL)-6 and IL-8 levels were significantly higher, declining over time and affecting the prognosis. CSF IL-6 and IL-8 levels were significantly elevated in the RSE group compared to patients without seizures and with controlled seizures, decreasing gradually and independently of serum cytokine levels. CSF IL-8 and age were independent risk factors for RSE, with clinical utility.ConclusionsPatients with SVE exhibit intrathecal cytokine storms, primarily characterized by elevated levels of IL-6 and IL-8, which influence prognosis. The strong and persistent hyperinflammation underscored by CSF IL-6 and IL-8 is associated with the occurrence and development of RSE; thus, CSF IL-8 and age are independent risk factors for SVE with RSE, indicating potential anti-inflammatory intervention targets.